Non-Invasive Genotyping of Honey Bee Queens Apis mellifera L.: Transition of the DraI mtDNA COI-COII Test to In Silico - Shayne Madella; Kyle Grubbs; Mohamed Alburaki (Insects, 2020)
The honey bee Apis mellifera L. colony is headed by a single and indispensable queen, whose duty it is to ensure brood production and provide pheromonal stability within the colony. This study presents a non-invasive method that allows the identification of the queen maternal lineage and subspecies using the remaining tissue of her clipped wing. The DraI mtDNA COI-COII (DmCC) test was applied to various sizes of queen and worker wings and the results were compared with data obtained from other bee tissues. Furthermore, we propose a new method allowing in silico transition of the DmCC test and haplotype identification based on extended sequencing of the tRNAleu and COII genes. Our results show that DNA extracted by Chelex 10% from one-third of a queen’s wing is deemed adequate for a successful identification of her maternal evolutionary lineage, haplotype and subspecies. The in silico method proposed in this study fully adheres to the established guidelines of the DmCC, provides a universal standard for haplotype identification, and offers faster and more precise results by reconciling both cleaved amplified polymorphic sequences (CAPS) and Sanger sequencing approaches.